2011
DOI: 10.1111/j.1468-3083.2010.03774.x
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of advanced dermatofibrosarcoma protuberans with imatinib mesylate with or without surgical resection

Abstract: We have confirmed the profound anti-tumour effect of imatinib in DFSP harbouring t(17;22) with long-term responses. Imatinib therapy may in some cases lead to tumour resectability of lesser disfiguration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
38
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(39 citation statements)
references
References 48 publications
0
38
0
1
Order By: Relevance
“…The PDGF receptor-selective oral tyrosine kinase-inhibitor imatinib (Glivec Ò ) is approved in Europe for the treatment of inoperable primary tumours, locally inoperable recurrent disease, and metastatic DFSP, with response in about 50% of treated patients. Imatinib has also been given to patients with extensive, difficult-to-operate tumours for preoperative reduction of tumour size [8,9], of whom fewer than half responded to treatment. This neo-adjuvant use of imatinib in DFSP should be confirmed by clinical trials before being widely accepted.…”
Section: Other Treatment Techniquesmentioning
confidence: 99%
“…The PDGF receptor-selective oral tyrosine kinase-inhibitor imatinib (Glivec Ò ) is approved in Europe for the treatment of inoperable primary tumours, locally inoperable recurrent disease, and metastatic DFSP, with response in about 50% of treated patients. Imatinib has also been given to patients with extensive, difficult-to-operate tumours for preoperative reduction of tumour size [8,9], of whom fewer than half responded to treatment. This neo-adjuvant use of imatinib in DFSP should be confirmed by clinical trials before being widely accepted.…”
Section: Other Treatment Techniquesmentioning
confidence: 99%
“…2,11,31 Imatinib, a competitive tyrosine kinase inhibitor, is currently approved by the Food and Drug Administration for the treatment of adult patients with unresectable, recurrent, and/or metastatic DFSP, and this may in turn facilitate tumor resection and or decrease disfigurement. 32 After local resection, the 5-year survival rate is 93-100%. 33,34 In agreement with these previously reported findings, none of the patients in our series had died of disease at the time of this report.…”
mentioning
confidence: 99%
“…[12][13][14]35 Most local recurrences occur within 3 years 11,12,35 ; only 30% occur after 5 years. 32 The lungs are the most common site of distant metastasis, 12,30,36,37 and metastasis has been reported to occur in 5-6% of cases. 13,14,34,35,38,39 Differential diagnoses of other cutaneous neoplasms that could be confused with DFSP include dermatofibroma, epidermal cyst, peripheral nerve sheath tumor, nodular fasciitis, cavernous hemangioma, liposarcoma, nodular type of melanoma, and mycosis fungoides.…”
mentioning
confidence: 99%
“…Imatinib is a tyrosine kinase inhibitor that has been registered for treatment of adult patients with inoperative and recurrent or metastatic DFSP, which are not suitable for surgery. In some studies it was confirmed that therapy with imatinib may significantly reduce the tumor volume and enable radical surgery [2,7].…”
Section: Discussionmentioning
confidence: 95%